BIOSURFACTANT THERAPEUTIC POTENTIALS: A REVIEW - Raji, Mudasiru I. O.; Bello, S. A. (FUDMA JOURNAL OF SCIENCES, 2024)
Natural products have proved to be an important source of novel antimicrobial agents and their uses in traditional medicine have brought about the discovery of several bioactive compounds. Biosurfactants are derived from many microorganisms and are classified as secondary metabolites. Some bacteria are capable of synthesizing chemical products that are essential in areas such as pharmaceuticals, biomedicine, and biotechnology. The study therefore reviews production of biosurfactants, their applications and unique physicochemical characteristics that make them suitable for commercial production of therapeutics. Biosurfactants different areas of exploit as antimicrobial agents and in drug delivery systems, are also reviewed. If well exploited, biosurfactants could be a potential candidate in the production of many therapeutics as well as biochemicals.